2008
DOI: 10.1051/vetres:2008015
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of the O157 urease-encoding O island 48 is present in porcine O149:H10 enterotoxigenicEscherichia coli

Abstract: -The relationship of the urease operon in the highly virulent O149 porcine enterotoxigenic Escherichia coli (ETEC) strain Ro8 to a genomic island (GI) homologous to O island (OI) 48 of O157 enterohemorrhagic E. coli (EHEC) strain EDL933 was investigated. Eighty-four of 84 O149:H10 strains were urease positive whereas 44 of 44 O149:H43 porcine ETEC strains were urease-negative. Seventeen of 17 O149:H10 strains that were tested possessed the OI-48 homolog whereas 24 of 24 O149:H43 strains lacked this OI. Transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…This region was similar to the urease-tellurite islands found in E. coli O157:H7 strains, EHEC O26:H11 strain 11368, and EHEC O111:H Ϫ strain 11128 (51). Previous studies have identified this island among porcine ETEC O149:K88 strains (39), and portions of this island in E. coli O157:H7 were shown to be involved in colonization to ligated pig intestine (56). Therefore, this island might be important for the colonization of UMNK88 and other K88 strains.…”
Section: Resultssupporting
confidence: 74%
“…This region was similar to the urease-tellurite islands found in E. coli O157:H7 strains, EHEC O26:H11 strain 11368, and EHEC O111:H Ϫ strain 11128 (51). Previous studies have identified this island among porcine ETEC O149:K88 strains (39), and portions of this island in E. coli O157:H7 were shown to be involved in colonization to ligated pig intestine (56). Therefore, this island might be important for the colonization of UMNK88 and other K88 strains.…”
Section: Resultssupporting
confidence: 74%
“…In the present study, a ureasenull mutant formed significantly fewer bacterial clusters than the wild-type EHEC O157:H7 parent strain, supporting a role for urease in virulence. Although urease is not expressed in vitro by most VTEC strains (5,6), it is likely that it is expressed in vivo, thereby contributing to bacterial survival in the intestine (6,19). This suggestion is supported by our RT-PCR data that show that ureC gene transcripts from the wild-type 86-24 strain present in pig ileal loops were detected at levels similar to those of the bacteria grown in BHIN broth static cultures in vitro (unpublished data).…”
Section: Discussionmentioning
confidence: 71%
“…Complementation of the urease-null mutant by introduction of the wild-type ure gene cluster on a plasmid failed to restore the wild-type adherence phenotype in the ligated pig ileal loops. It is possible that regulation of urease synthesis might have prevented the plasmid-encoded urease from expression in the host intestine as regulation of ure expression appears complicated by unknown trans-acting factors (9,19). On the other hand, it might be the negative effect from overexpression of urease in the complemented strain as it was also observed that the complemented mutant 86-24⌬ureC (pUDG) caused even less adherence to IPEC-J2 cells than its parent mutant (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Urease genes were detected in the major EHEC groups O26, O111, and O157, as well as in sorbitolfermenting EHEC O157:NM strains, but were absent from diarrheagenic E. coli strains of several other pathogroups, including enteroaggregative E. coli, enteroinvasive E. coli, and EPEC strains (18,40). In enterotoxigenic E. coli, there is a homologue of the O157 urease-encoding OI-48 (46). These investigations indicate the virulence potential of urease in EHEC.…”
Section: Discussionmentioning
confidence: 74%